140 YEARS OF THE UNIVERSITY HISTORY (Interview with the Rector of BelSU O.N. Polukhin) - Editorial Article (Высшее образование в России, 2016)
In his interview the Rector of Belgorod State National Research University O.N. Polukhin highlights its main achievements, competitive advantages, prospects of development. Prof. O.N. Polukhin dwells on the University academic reputation and position in world rankings.